(untitled) (Baghdad Science Journal, 2013)
The antibacterial activity of some extracts of A. eupatoria (aqueous and ethanolic) against some pathogenic bacteria (Staphylococcus aureus, Pseudomonas aeruginosa and Escherichia coli ) and their activity on wound healing in rats , also the presence of some active compounds in both extracts were detected . The results showed that the ethanolic extract was more effective on inhibiting tested bacteria than the aqueous extract . P.aeruginosa was the most resistant bacteria, while highest inhibition zone appeared on E.coli (20 mm) .There was a moderate activity against S.aureus with inhibition zone 15 mm. by using ethanolic extract (10 mg/ml) . The phytochemical analysis for detection of active compounds revealed the presence of Carbohydrates, Glycosides and Tannins in both extracts, while some of compounds such as Terpenoids and Phenolic compounds (flavonoids) were detected in the ethanolic but not in the aqueous extracts. Prepared ethanolic extract ointment presented obvious activity on wound healing activity in rats in contrast with fucidin ointment and aqueous extract ointment, hence the wound healing was completed in l0 days by using the ethanolic extract ointment, while it was 12 days and 14 days for the aqueous extract ointment and fucidin ointment respectively, in comparison with the untreated wound which needed more than 16 days for healing completion.